Espiritualidade dos estudantes e residentes de Medicina: associações com empatia e atitude na relação médico-paciente - Lacombe, Julianni Bernadelli (2017)
Background: Studying the factors that improve interpersonal relationships in patient care and medical education has been considered relevant and necessary. Understanding what predicts empathy among students and medical residents attitudes is a relevant issue in the education of health professionals. Although patients and medical students have pointed spirituality as an important issue, it is not frequently addressed in medical schools. Objective: To verify the association between students’ and medical residents’ well-being related to spirituality, religiousness and personal beliefs and students’ and medical residents’ empathy and attitudes in the physicianpatient relation. Methods: Cross-sectional, observational study with a total of 64 students and 50 residents. Participants answered to the following self-administered instruments: WHOQOL-Spirituality, Religiousness and Personal Beliefs, Jefferson Scale of Empathy, and Patient-Practitioner Orientation Scale. Descriptive statistics, Spearman correlation and stepwise linear regressions were used to analyze data. The level of significance was p <0.05. The Cronbach alpha was used to verify the internal consistency of the instruments. Results: Moderated correlations with r > 0.3 p < 0.05 were found: Perspective-taking: Spiritual Connection (r = 0.309; p < 0,01), Experiences of Awe and Wonder (r = 0.306; p < 0.01), Wholeness and Integration (r = 0.342; p < 0.01), Spiritual Strength (r = 0.309; p < 0.01) and WHOQOL-SRPB global score (r = 0.394; p < 0.01); Final JSE score: Wholeness and Integration (r = 0.337; p < 0.01), Inner Peace (r = 0.325; p < 0.01) and WHOQOL-SRPB global score (r = 0.352; p < 0.01); Sharing: Wholeness and Integration (r = 0.334; p < 0.01); Caring: WHOQOLSRPB global score (r = 0.312; p < 0.01); PPOS Total score: Meaning and Purpose in Life (r = 0.323; p < 0.01), Experiences of Awe and Wonder (r = 0.336; p < 0.01), Wholeness and Integration (r = 0.364; p < 0.01), Inner Peace (r = 0.315; p < 0.01) e WHOQOL-SRPB global score (r = 0.358; p < 0.01). WHOQOL-SRPB final score affected the global score of empathy (R2=0.12; p<0.01; β=0.35; VIF=1.00). The facet Meaning and Purpose in Life affected the global score of the patient-centered attitude (R2=0.14; p <0.01; β=0.38; VIF=1.00). Conclusions: Spirituality, religiousness and personal beliefs are associated with medical students’ and residents’ empathy and patient-centered attitudes. Well-being related to spirituality was a predictor of empathy, and Meaning and Purpose in Life predicted patient-centered attitudes. These results imply the need to consider well-being related to spirituality in medical education for a better physician-patient relation.